2011
DOI: 10.1371/journal.pone.0019831
|View full text |Cite
|
Sign up to set email alerts
|

Mice Lacking NKT Cells but with a Complete Complement of CD8+ T-Cells Are Not Protected against the Metabolic Abnormalities of Diet-Induced Obesity

Abstract: The contribution of natural killer T (NKT) cells to the pathogenesis of metabolic abnormalities of obesity is controversial. While the combined genetic deletion of NKT and CD8+ T-cells improves glucose tolerance and reduces inflammation, interpretation of these data have been complicated by the recent observation that the deletion of CD8+ T-cells alone reduces obesity-induced inflammation and metabolic dysregulation, leaving the issue of the metabolic effects of NKT cell depletion unresolved. To address this q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 28 publications
4
83
3
Order By: Relevance
“…Strikingly, glucose tolerance measured via an intraperitoneal glucose tolerance test (IP-GTT) was clearly impaired in the CD1d-null mice compared with their WT counterparts, especially under LFD conditions (Figure 1, D-G). Under HFD conditions, CD1d-null mice showed higher insulin levels during the IP-GTT than their WT counterparts, but maintained comparable glucose levels (Figure 1, D-G), in accordance with previous studies (26)(27)(28). To corroborate these findings, we used of Jα18-null mice, which are selectively deficient in type 1 iNKT cells (31).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Strikingly, glucose tolerance measured via an intraperitoneal glucose tolerance test (IP-GTT) was clearly impaired in the CD1d-null mice compared with their WT counterparts, especially under LFD conditions (Figure 1, D-G). Under HFD conditions, CD1d-null mice showed higher insulin levels during the IP-GTT than their WT counterparts, but maintained comparable glucose levels (Figure 1, D-G), in accordance with previous studies (26)(27)(28). To corroborate these findings, we used of Jα18-null mice, which are selectively deficient in type 1 iNKT cells (31).…”
Section: Resultssupporting
confidence: 88%
“…Indeed, some recent reports indicate that depletion of iNKT cells can improve insulin sensitivity under HFD conditions (59)(60)(61). The exact role of iNKT cells under HFD conditions is, however, unclear, as other studies, and the present study, failed to detect a prominent effect of iNKT cell depletion on glucose homeostasis (26)(27)(28). Of note, the decreased number of AT-resident iNKT cells in obese human individuals and in mice under long-term HFD conditions may explain the marginal effects of iNKT cell depletion under HFD conditions (refs.…”
Section: Methodscontrasting
confidence: 51%
See 1 more Smart Citation
“…NKT cells react to lipid antigens presented on CD1d, which results in the secretion of various cytokines (IL-4, IL-10, IFN-g, and TNF-a) that may elicit Th1, Th2, and Treg responses. Experiments with mice with loss-and gain-offunction in NKT activity revealed a gamut of outcomes ranging from beneficial (21)(22)(23)(24)(25), to null (26), to detrimental (27)(28)(29) effects of NKT cells on metabolism. These divergent effects may result from the various strategies applied (CD1d 2/2 that affects all NKT cells vs. Ja18 2/2 that affects only type 1 NKT cells), various diets, various durations, or other local, yet not identified factors.…”
Section: Immune Cells Orchestrate the Outcome Of At Inflammationmentioning
confidence: 99%
“…NKT cells could contribute to the development of visceral WAT inflammation during obesity, since HFD-fed NKT-deficient mice (β 2 -microglobulin knockout mice) show lower macrophage accumulation and better glucose tolerance than control mice, with no differences in body weights [65]. However, it has recently been demonstrated that the aforementioned effects of NKT cell deletion on metabolism can only occur in the absence of CD8 + T cells [66]. Moreover, previous studies have reported that adoptive transfer or agonist activation of NKT cells ameliorate the metabolic dysregulation of the ob/ob mice [55,67], suggesting that the role of NKT cells in obesity-related inflammation may be complex.…”
Section: Regulatory T Cellsmentioning
confidence: 99%